Persistent Summer North Atlantic Jet Variability: Dynamical Feedbacks and Model‐Observation Discrepancies - Albert Ossó; Florian Ennemoser (Geophysical Research Letters)
Abstract Persistent fluctuations in the latitudinal position of the North Atlantic (NATL) jet stream are closely linked to extreme weather anomalies, particularly over Europe. Accurately representing jet stream persistence in climate models is essential for enhancing the reliability of future regional extreme weather projections. This study investigates the summer persistence of the NATL jet stream latitudinal fluctuations and the Summer North Atlantic Oscillation (SNAO) using data from CMIP6 models and ERA5 reanalysis. Our findings reveal that CMIP6 models generally overestimate persistence compared to ERA5 during the historical period. Utilizing the relative vorticity tendency equation, we assess the strength of the eddy‐mean flow feedback and identify a positive relationship between persistence and feedback strength across models. We also found that a large fraction of the intermodel spread in precipitation persistence is associated with differences in the persistence of jet fluctuations.